Book review: The Ibadis in the Region of the Indian Ocean. Section One : East Africa, written by Heinz Gaube - Prevost, Virginie (Arabica, 2015)
"Book review: The Ibadis in the Region of the Indian Ocean. Section One : East Africa, written by Heinz Gaube" published on 04 Mar 2015 by Brill.
Keywords: Recension

Book review: Oman and Overseas éd. Michaela Hoffmann-Ruf et Abdulrahman al-Salimi, written by Oman and Overseas - Prevost, Virginie (Arabica, 2015)
"Book review: Oman and Overseas éd. Michaela Hoffmann-Ruf et Abdulrahman al-Salimi, written by Oman and Overseas" published on 04 Mar 2015 by Brill.
Keywords: Recension